THE ROLE AND IMPORTANCE OF AGRICULTURE IN THE DEVELOPMENT OF THE NATIONAL ECONOMY OF THE REPUBLIC OF UZBEKISTAN - Saydullaeva Saodat; Nurullaeva Shakhnoza; Muminova Maxbuba Abduvafoyevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This scientific article focuses on the analysis of a certain level of contribution of agricultural production to the positive changes in the national economy of the republic in 2018-2019. There is a general approach to the role of the industry in strengthening the food security of products, as well as in the supply of raw materials for the light industry and solving the problem of unemployment in the country.